2014
DOI: 10.1080/03601234.2014.911593
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural changes in the rabbit liver induced by carbamate insecticide bendiocarb

Abstract: Carbamates (CB) are used as insecticides and some of them have been registered as human drugs. The mechanism of CB poisoning involves reversible inhibition of acetylcholine esterase. In the present study, we investigated changes in liver ultrastructure in rabbits (Oryctolagus cuniculus) which were administered bendiocarb for 3, 10, 20, and 30 days. Rabbits in all experimental groups received capsules of bendiocarb (96% Bendiocarb, Bayer, Germany) per os daily at a dose of 5 mg/kg of body weight, and after day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 32 publications
(33 reference statements)
1
9
0
3
Order By: Relevance
“…Bendiocarb was shown to alter homeostasis (Capcarova et al 2010;Mojzisova et al 2012) and induce morphological changes in different organs such as the thymus, kidneys, and liver (Flesarova et al 2007;Almášiová et al 2014;Holovska et al 2014). In agreement with previously published studies, it can be concluded that bendiocarb adversely affected the structure of rabbit tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Bendiocarb was shown to alter homeostasis (Capcarova et al 2010;Mojzisova et al 2012) and induce morphological changes in different organs such as the thymus, kidneys, and liver (Flesarova et al 2007;Almášiová et al 2014;Holovska et al 2014). In agreement with previously published studies, it can be concluded that bendiocarb adversely affected the structure of rabbit tissues and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Keracunan karbamat dapat terjadi melalui inhalasi, gastrointestinal (oral) atau kontak kulit (Gupta, 2014). Karbamat dapat menimbulkan efek toksik melalui hambatan enzim asetilkolinesterase (AChE) pada sinapsis syaraf dan myoneural junctions yang bersifat reversibel (Holovska et al, 2014). Selain menghambat aktivitas AChE, karbamat juga telah dilaporkan dapat menyebabkan perubahan fungsional dan histologis setelah pajanan jangka panjang dan dosis tinggi pada kulit, mata, hemoepoitik, ginjal, testis, dan hati (Gupta, 2014).…”
Section: Pendahuluanunclassified
“…Hal ini membuktikan bahwa pemberian karbamat secara oral dengan dosis 10 mg/kgBB selama 14 hari dapat menimbulkan kerusakan pada jaringan hati tikus. Temuan ini sesuai dengan penelitian yang dilakukan oleh Barfield-Burlinson (2015) dan Holovska (2014) bahwa karbamat dapat menyebabkan kerusakan pada jaringan hati. Penghambatan AChE yang diakibatkan oleh karbamat akan menyebabkan penumpukan asetilkolin, dan menyebabkan pembetukan NO menjadi tidak terkontrol, kemudian NO akan menyebabkan kerusakan sel melalui beberapa cara, yaitu, NO yang berlebih tidak seimbang dengan antioksidan tubuh sehingga masih banyak NO dalam bentuk bebas, dan cenderung berikatan dengan O2membentuk ONOO-, ONOO-memiliki sifat senyawa radikal yang sangat kuat yang dapat menimbulkan lipid peroksidasi (Radi et al, 1991;Cross et al, 1998).…”
Section: Pembahasanunclassified
See 1 more Smart Citation
“…Carbamates are one of the most frequently applied pesticides, commonly used in household and agricultural pest control [2][3][4]. WHO also recommends carbamates for malaria control [5][6][7][8], although various carbamate compounds are more toxic to vertebrates than other groups of pesticides [9]. Bendiocarb (2,2-dimethyL,3-benzodioxol-4-yl-Nmethylcarbamate) belongs to the widely used carbamate compounds.…”
Section: Introductionmentioning
confidence: 99%